Estuaries and Coasts - Estuaries and Coasts (Springer Nature, 2026)
Publishes peer-reviewed research on estuarine and nearshore coastal ecosystems located at the interface between land and sea, particularly where tidal influence or freshwater–seawater mixing occurs. The journal covers physical, chemical, geological, and biological processes, as well as their interactions and applications to coastal and estuarine management. It includes studies on environments such as lagoons, wetlands, tidal freshwater systems, shores, and beaches, and publishes original research articles, reviews, perspectives, techniques, and management applications.
FI 0.68
Q3
Keywords: Earth; Space & Environmental Sciences; Environmental Science; Ciencia ambiental; Acuerdos transformativos; Transformative agreements; Estuarios; Aguas costeras; Procesos físicos